1995
DOI: 10.1007/bf01075913
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of peroxovanadium compounds relevant to insulin mimesis

Abstract: The inorganic coordination chemistry of peroxovanadium compounds relevant to insulin mimesis is reviewed. The structure and kinetic reactivity of solutions of vanadate anion, vanadyl complexes and peroxovanadate complexes are briefly compared. Peroxovanadium compounds contain an oxo group, one or two peroxo ligands (O2(2-)) and an ancillary ligand which is usually bidentate. These compounds approximate a trigonal bipyramidal structure which can be divided conceptually into a polar 'oxo' half and a relatively n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…(88 -90). The greater efficacy of vanadate is also consistent with its trigonal bipyramidal structure, which resembles phosphate more closely than the tetrahedral geometry of vanadyl (57,62). In a recent study, Cuncic et al (60) reported that cultured Jurkat T-lymphoma cells, which were unresponsive to vanadate, became sensitive to stimulation of protein tyrosine phosphorylation after GSH depletion.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…(88 -90). The greater efficacy of vanadate is also consistent with its trigonal bipyramidal structure, which resembles phosphate more closely than the tetrahedral geometry of vanadyl (57,62). In a recent study, Cuncic et al (60) reported that cultured Jurkat T-lymphoma cells, which were unresponsive to vanadate, became sensitive to stimulation of protein tyrosine phosphorylation after GSH depletion.…”
Section: Discussionmentioning
confidence: 49%
“…Whether the more oxidized form vanadate (ϩ5) or reduced form, vanadyl (ϩ4) is the more important and relevant insulinmimetic form in intact cells and in vivo has been controversial (59,62,69). Thus, in some studies it was demonstrated that a cytosolic Tyr kinase was activated by vanadate (ϩ5) while vanadyl (ϩ4) directly inhibited receptor Tyr kinases including the IR kinase (59).…”
Section: Discussionmentioning
confidence: 99%
“…7,41,42 Peroxovanadates have been reported to affect cellular signaling by influencing the functioning of a number of enzymes including mitogenactivated protein kinase (MAPkinase), tyrosine phosphatases, phospholipase D. 7,43,44 It has been suggested that the inhibitory action of vanadate and pV on protein phosphatase hydrolysis may be an important part of their insulin-like effect. 35,45 Enzyme inhibition has already been identified as an important pathway for the action of inorganic drugs and remains an area needing further exploration. 46 Apart from peroxovanadates (pV), molybdate and peroxomolybdate (pMo) as well as tungstate and peroxotungstate (pW) have also been reported as potential insulin mimics with an ability to inhibit the activity of phosphoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…16 Among the various d o transition metal peroxo systems, V(V), Mo(VI) and W(VI), which have clear structural and isoelectronic relationships, attract continuous research attention because of their versatility and selectivity as stoichiometric or catalytic oxidizing or oxo-transfer agent in a variety of organic oxidations such as epoxidation of alkenes, [17][18][19][20] oxidation of sulfides and sulfoxides, [21][22][23][24][25][26] primary and secondary alcohols, 27,28 as well as halide oxidation. [29][30][31][32] Besides these, the active involvement or relevance of these peroxometallates in haloperoxidase, 29,31,32 their insulino-mimetic, [33][34][35][36] anti-neoplastic 37 and enzyme inhibitory activity 38,39 have been well documented. The vanadium-dependent bromoperoxidase (V-BPO) is now the subject of tremendous interest for chemists as well as biologists.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of synthetic pV compounds with different ancillary ligands have been tested in recent years for their possible insulin like behavior [5,8,9,13] and affinity as inhibitors of phosphoproteins [2][3][4]. However, most of these compounds are hydrolytically unstable which limits their utility as therapeutic agents [4,7,9].…”
Section: Introductionmentioning
confidence: 99%